What knowledge about what environment? - Scholz, Roland W. (Environmental Literacy in Science and Society, 2011)
Chapter overviewHumans’ concerns about and interactions with the environment, from navigating the seas to managing a farm or operating a nuclear power plant, have emerged from the core need to survive by using environmental information and resources. This chapter explores the emerging awareness of the environment as a prelude to understanding human interactions with the environment. Central to this discussion is environmental literacy – the human aptitude for appropriately reading and using environmental information to use environmental resources properly and to adapt effectively to environmental dynamics. This chapter reveals what knowledge about the environment is relevant, what environmental literacy means, and introduces the drivers and rationales underlying environmental awareness.